Reinterpreting a Prophetic Hadith for Student Resilience: A Hermeneutic and Psychopedagogical Approach - Susetyo, Marwal Blantara; Sumarna, Elan; Surahman, Cucu; Ali Husaeni, Muhammad Fahri; Abdillah, Moch Silmi (Suhuf: International Journal of Islamic Studies, 2026)
Background: The "strawberry generation" phenomenon among students in the digital era is characterized by a low tolerance for pressure and a high dependence on external validation. Objective: This study aims to reconstruct the concept of strengthening Religious Resilience through an analysis of Sahih al-Bukhari Hadith No. 71. Methodology: This qualitative library research employs Fazlur Rahman's Double Movement Hermeneutics approach integrated with psychopedagogical analysis. Results: The First Movement reveals "la yadhurruhum man khalafahum" as a doctrine of psycho-spiritual immunity. Through the Second Movement, this study synthesizes a comparison between Western resilience (anthropocentric) and Islamic resilience (theocentric), reconstructing the hadith into an active defense mechanism that fosters a Theocentric Internal Locus of Control. Conclusion: This hadith offers a vital psychopedagogical blueprint, transforming theological doctrine into an active psychological defense to build a resilient Climber mentality (AQ) in students. The findings offer a concrete Instructional Design to internalize resilience values through vicarious learning, religious assertiveness training, and social lab simulations, enabling students to courageously uphold the truth.